VITAMIN D DEFICIENCY IN GAIT AND COGNITION. LESSONS LEARNED FROM THE GAIT & BRAIN STUDY - MonteroOdasso, M. (Innov Aging, 2017)
This talk will review recent provocative studies that have demonstrated relationships between Vitamin D deficiency with poor cognitive and mobility performance in older adults. Interventional studies supplementing vitamin D have shown mixed result concerning cognitive and mobility outcomes. Results from the GAIT & BRAIN Study and from a recent meta-analysis will be presented showing that Vitamin D supplementation in doses higher that the current recommendation of 800 IUd/d would be needed to achieve serum levels over 75nml/l which seems needed to improve cognitive and mobility outcomes in older adults with Vitamin D deficiency. Potential neuroprotective vitamin D attributes through antioxidative mechanisms, neuronal calcium regulation, immunomodulation, enhanced nerve conduction and detoxification mechanisms will be reviewed.